Students' Skills to Solve Linear Equation System in Two Variables: Systematic Literature Review - Rodiana, Ivta; Hamdiyanti, Meti; Laelasari, Laelasari; Subroto, Toto (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Riau, 2024)
The system of linear equations of two variables is contextual material in learning mathematics. Yet, there are facts that show there are still errors and difficulties experienced by students in the problem of the system of linear equations of two variables. The research purpose is to conduct a literature review on the skills, errors, and difficulties of students on the problem of the system of linear equations of two variables. This research uses the SLR (Systematic Literature Review) method. Data collection was carried out by reviewing all articles related to math skills, errors, and difficulties of students on the problem of the system of linear equations of two variables published from 2019 to 2023. Based on the research results, it was found that students' skills to solve the problem of two-variable linear equation system was still low. Students still made many mistakes in understanding the problem and converting it into a mathematical model, carrying out the plan or process, performing calculations, and often ignoring the evaluation of the results obtained.